2020
DOI: 10.1002/ange.202001922
|View full text |Cite
|
Sign up to set email alerts
|

A Pressure‐Induced Inverse Order–Disorder Transition in Double Perovskites

Abstract: Given the consensus that pressure improves cation ordering in most of knownm aterials,ad iscovery of pressureinduced disordering could require recognition of an orderdisorder transition in solid-state physics/chemistry and geophysics.D ouble perovskites Y 2 CoIrO 6 and Y 2 CoRuO 6 polymorphs synthesized at 0, 6, and 15 GPas howB -site ordering, partial ordering, and disordering, respectively,accompanied by lattice compression and crystal structure alteration from monoclinic to orthorhombic symmetry.C orrespond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…High pressure experiments were performed with the cubic anvil type high pressure apparatus 34,35 . After the pressure was gradually increased to 6 GPa, the sample was heated to 1273 K and maintained for 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…High pressure experiments were performed with the cubic anvil type high pressure apparatus 34,35 . After the pressure was gradually increased to 6 GPa, the sample was heated to 1273 K and maintained for 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Hazen and Navrotsky (1996) analysed the influence of pressure upon order–disorder reactions and showed that, in the majority of cases, increasing pressure is associated with decreasing positional disorder, though there are exceptions to this rule (Deng et al , 2020). The ordering reactions mean that structural complexity is increasing.…”
Section: Further Directionsmentioning
confidence: 99%